The Archetype of Graphic Thinking. Visual Graphic Tool that Analyses the Graphic, Creative and Project Thinking of the Product Designer - Barban Franceschi, Roberta (Springer Series in Design and Innovation, 2023)
The evolution of technology towards digital and abstract possibilities combined with the evolution of culture and the intricacies of technology empower the designer’s role in the design process. The virtualization of the world is a reality throughout society and a decisive factor in various sectors of design. This article introduces a tool created to analyse the graphic thinking involved in a project, and the participation of new technologies in the designer’s creative process and graphic representation of his ideas. A core (the designer) that is connected to three small networks: graphic thinking, creative thinking, and project thinking, forms the archetype of graphic thinking. Outstanding designers and theoreticians in the field of project methodology, creativity and graphic representation, have been studied for the making of this tool. This visual graphic tool can identify the changes in the creative process and its materialization, as well as verify to what extend new technologies have paved the way not only for a change in the thinking process, but also in design.
Keywords: creative; design process; graphic thinking; technology; visual graphic tool; visual thinking; Scopus(2)